Analisis Faktor – Faktor Yang Mempengaruhi Terjadinya Turnover Perawat Honorer Di RS TNI – AD Kota Padangsidimpuan Tahun 2019 - Sri Sudewi Pratiwi Sitio; Ripai Siregar; Efrata Sembiring (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Nurse turnover is the discharge of nurses from one hospital to another which is considered better than the previous hospital. The purpose of this study was to determine what factors influence the turnover of honorary nurses at the TNI - AD Hospital with a cross sectional research design. The total population and sample of the study were 78 nurses. The research instrument used was a questionnaire. Data analysis used univariate method, bivariate with chi square test and multivariate with logistic regression test. The results showed that from 78 nurses as many as 67 (85.9%) said that the basic salary received was not proportional to the workload they did. The basic salary received is still the minimum regional wage so that it can lead to turnover for honorary nurses. The factor of turnover based on incentives was 42 nurses (53.8%) with categories still below Rp. 500,000 received, 69 nurses (88.5%) had never experienced a promotion during work and 66 nurses (84.6%) had never experience work conflict. The results of the bivariate analysis obtained are that the factors that influence the occurrence of turnover are basic salary with a p value of <0.05. The results of multivariate analysis showed that basic salary was the most dominant factor in the occurrence of turnover in honorary nurses with a coefficient value (10,034). Policies are needed in fair promotion and re-evaluation of the compensation system in accordance with the length of work and level of education.